Distress symptoms, anxiety, depression level, and self-care ability of oncology inpatients in a Region of Turkey - Koç, Zeliha; Şener, Asuman (European Journal of Oncology and Environmental Health, 2017)
Background and aim of the work: Although cancer diagnosis and treatment induce distress, anxiety, and depression, these symptoms are not efficiently diagnosed by healthcare professionals until expressed by patients. In this research, it was aimed to detect the factors affecting distress symptoms, anxiety, depression, and self-care ability among oncology inpatients. Methods: This descriptive cross-sectional study was conducted in the oncology department of a research hospital located in the Central Black Sea Region in the north of Turkey. A total of 356 patients participated. Data were collected via a 29-item questionnaire and the Hospital Anxiety and Depression Scale, Symptom Distress Scale, and Self-care Ability Scale. Results: It was found that 61.8% of patients were at risk of anxiety and 76.4% were at risk of depression. The total mean score for the Symptom Distress Scale was 38.91±15.02 and that for the Self-care Ability Scale was 79.5±22.6. The highest scores on the Symptom Distress Scale were observed for severity of pain (3.43±1.34), fatigue (3.38±1.29), and frequency of pain (3.32±1.33). Conclusions: This study showed that distress prevalence among oncology patients is 78.6%; patients perceived their self-care ability to be at a medium level. Moreover, 84.3% of patients resorted to complementary treatments (herbal treatment, regulating diet, praying) in order to alleviate or mitigate the symptoms they experienced.